Manufacturing method of fine blasting beads

Through the coordinated use of high-precision microjet equipment and laser particle size analyzer, combined with strict raw material screening and refined operation, the various shortcomings in the production of fine blast beads in the existing technology have been solved, the high quality and performance improvement of the product has been achieved, and the demand of the high-end market has been met.

CN119771287AActive Publication Date: 2025-04-08GUANGDONG WONDERFUL INT BIOTECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510140656.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-08
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing fine blast bead production technology has obvious shortcomings in particle size control, raw material treatment, curing reaction, cleaning and drying, production equipment and quality control, which makes it difficult to improve product quality and performance, limiting its wide application in the food and tobacco products industry.

Method used

Through the precise cooperation of high-precision microjet equipment and laser particle size analyzer, real-time monitoring and precise control of droplet particle size is achieved, and a strict quality control system is established by combining strict core and wall screening and pretreatment, as well as refined curing, cleaning and drying operations.

Benefits of technology

It significantly improves the uniformity and consistency of small explosive bead products, ensures high quality and performance of the products, and meets the high-quality requirements of the high-end market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005264737510000111
    Figure BDA0005264737510000111
Patent Text Reader

Abstract

The invention relates to the technical field of microencapsulated small blasting bead manufacturing, in particular to a small blasting bead manufacturing method which comprises the following steps: preparing a high-purity core material, gelatin and an Arabic gum wall material, and blending according to the ratio of 2.5: 1; micro liquid drops are formed by adopting a microencapsulation technology, and the particle size is regulated and controlled to be 0.5-2.0 mm; and adding glutaraldehyde for curing, reacting at the pH value of 6.5, carrying out low-temperature centrifugal cleaning, blow-drying by using nitrogen, and carrying out vacuum drying until the water content is lower than 4.5%, so as to obtain the fine blasting bead finished product with qualified particle size. The high-precision micro-jet equipment is precisely matched with the laser particle size analyzer, so that the real-time monitoring and precise control of the particle size of the liquid drops are realized; according to the technical scheme, the particle size of more than 96% of liquid drops is ensured to be within the ideal range of 0.5-2.0 mm, so that the uniformity and consistency of the blasting bead product are remarkably improved, and meanwhile, the quality and performance of the product are further ensured through strict screening and pretreatment of the core material and the wall material and fine operation of key steps such as curing, cleaning and drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of manufacturing microencapsulated fine bursting beads, in particular to a method for manufacturing the fine bursting beads. Background Art

[0002] In the food and tobacco products industry, small popping beads are an important additive or independent product, and their production technology has always been the focus of attention in this field. However, the existing small popping beads production method has obvious shortcomings in many aspects.

[0003] First, in terms of particle size control, traditional technologies often rely on empirical judgment or simple mechanical operations, resulting in a wide range of particle size distribution of popping beads, making it difficult to achieve ideal consistency and uniformity. This not only affects the appearance and taste of the product, but also limits its application in the high-end market.

[0004] Secondly, the operation of key steps such as raw material processing and curing reaction also lacks sufficient refinement. Traditional methods often ignore the pretreatment and purification of raw materials, as well as the precise control of curing reaction conditions, which may lead to instability of the internal components of the beads and affect the quality and performance of the product.

[0005] In addition, traditional technologies also have many defects in the cleaning and drying process. For example, incomplete cleaning may cause impurities to remain on the surface of the beads, while uneven drying may damage the integrity and stability of the beads.

[0006] More importantly, the traditional method of making small popping beads lacks efficient production equipment and a strict quality control system, which makes production efficiency low and product quality difficult to be stably guaranteed.

[0007] In summary, the existing fine popping bead production technology has obvious deficiencies in terms of particle size control, raw material processing, curing reaction, cleaning and drying, production equipment and quality control. These shortcomings limit the improvement of the quality and performance of popping bead products and also hinder their wide application in the food and tobacco products industry. Therefore, a new method for producing fine popping beads is urgently needed to solve these problems in the existing technology. Summary of the invention

[0008] Technical issues solved

[0009] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for producing fine bursting beads. The present invention realizes real-time monitoring and precise control of droplet particle size through precise coordination of high-precision microfluidic equipment and laser particle size analyzer, ensuring that more than 96% of the droplet particle size is within the ideal range of 0.5-2.0 mm, thereby significantly improving the uniformity and consistency of the bursting bead products. At the same time, strict screening and pretreatment of core materials and wall materials, as well as refined operations of key steps such as curing, cleaning and drying, further ensure the quality and performance of the products. This scientific and rigorous production method provides a strong guarantee for the preparation of high-quality fine bursting beads.

[0010] Technical Solution

[0011] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0012] A method for making small explosive beads, the method comprising the following steps:

[0013] First, prepare the core material and wall material raw materials. The core material is a liquid substance containing specific functional ingredients. The purity is tested by gas chromatography-mass spectrometry to ensure that the purity reaches 99.5%. Edible gelatin and gum arabic are used as the wall material and are prepared at a mass ratio of 2.5:1.

[0014] Next, the microencapsulation technology is used to inject the core material into the wall material solution at a frequency of 150 times per second through a high-precision microfluidic device. At the same time, the temperature is controlled at 27°C and the stirring speed is 400 revolutions per minute, so that the core material forms tiny droplets in the wall material solution. The droplet size distribution is monitored in real time using a laser particle size analyzer. When the particle size is greater than 2.0 mm, the pressure of the microfluidic device is increased by 0.7 MPa / time, and when the particle size is less than 0.5 mm, the pressure is reduced by 0.4 MPa / time, ensuring that more than 96% of the droplet size is between 0.5 and 2.0 mm.

[0015] Subsequently, a curing agent is added to the mixed solution containing the droplets. The curing agent is glutaraldehyde, and the addition amount is 0.7% of the weight of the wall material. The dropping speed is 3 drops per minute. At the same time, the mixture is stirred at a speed of 120 revolutions per minute. The mixture is reacted for 45 minutes in an environment with a pH value of 6.5, so that the wall material forms a shell on the surface of the core material.

[0016] Finally, a low-temperature centrifugal cleaning device is used to clean at a speed of 1200 revolutions per minute and a temperature of 6°C for 12 minutes, and then deionized water is used for cyclic cleaning 5 times. The cleaning liquid is considered qualified if the impurity content is less than 8 mg / L after cleaning. After cleaning, it is blown dry with nitrogen and then placed in a vacuum drying oven with a vacuum degree of -0.095 MPa and a temperature of 45°C for 4 hours. A Karl Fischer moisture meter is used for monitoring. When the water content is lower than 4.5%, the drying is stopped to obtain fine burst beads with a particle size of 0.5-2.0 mm.

[0017] Furthermore, the preparation process of the core material further includes: pre-treating the core material raw material, wherein the core material is a liquid substance containing volatile components, and is stored and prepared in a sealed environment at a temperature controlled at 5°C. During the preparation process, high performance liquid chromatography analysis is used to accurately control the proportion of each component, and the error is controlled within ±0.3%. The pre-treated core material is filtered using a microporous filter membrane with a pore size of 0.3μm to remove any tiny particle impurities.

[0018] The method for making fine explosive beads according to claim 1 is characterized in that the preparation process of the wall material further includes: adding gelatin and gum arabic to deionized water at a mass ratio of 2.5:1, stirring and dissolving at a temperature of 55°C at a speed of 250 revolutions per minute for 75 minutes to form a uniform solution, using a vacuum degassing device, degassing for 15 minutes under a vacuum degree of -0.09MPa to remove bubbles in the solution, and after degassing, detecting the viscosity of the solution by a viscosity meter to ensure that its viscosity is 25mPa·s, so as to ensure that the core material droplets can be well wrapped in the subsequent microencapsulation process.

[0019] Furthermore, during the microencapsulation process, the number of air dust particles in the reaction area is controlled below 8,000 per cubic meter through air purification equipment to prevent the mixing of external impurities. At the same time, a high-speed camera is used to shoot the droplet formation process at a speed of 500 frames per second, and the droplet morphology and particle size changes are dynamically analyzed with image analysis software, and the pressure of the microjet equipment is further accurately adjusted to ensure precise control of the droplet particle size.

[0020] Furthermore, during the curing process, the temperature and pH value changes of the reaction system are monitored in real time by a temperature sensor and a pH sensor. When the pH value deviates from 6.5±0.2, disodium hydrogen phosphate-citric acid buffer solution is automatically added for adjustment to ensure that the curing reaction proceeds stably and forms a strong and uniform wall material shell.

[0021] Furthermore, during the cleaning process, the low-temperature centrifugal cleaning equipment uses a variable frequency speed regulation motor to ensure a stable rotation speed during the cleaning process. After the cleaning is completed, the surface of the beads is observed by a scanning electron microscope to ensure that there are no residual impurities. When nitrogen is used for drying, the nitrogen pressure is controlled at 0.2MPa and the drying time is 10 minutes.

[0022] Furthermore, an infrared temperature sensor is arranged in the vacuum drying box to monitor the temperature at different positions of the blasting beads in real time to ensure that the blasting beads are heated evenly. After drying, an electronic universal material testing machine is used to test the strength of the blasting bead shell, and a nuclear magnetic resonance spectrometer is used to test the core material content to ensure that the finished blasting beads meet the requirements of a particle size of 0.5-2.0 mm and various performance indicators are qualified.

[0023] Furthermore, during the entire production process, the production equipment is regularly maintained and calibrated, and the mechanical parts of the microfluidic equipment, stirring device and centrifugal cleaning equipment are inspected and maintained once a week, including but not limited to checking the wear of the transmission parts and the sealing of the sealing parts. The measuring instruments of the equipment, including but not limited to pressure sensors, temperature sensors and viscometers, are calibrated monthly using standard measuring instruments to ensure that the error of the measurement data is within ±0.5%.

[0024] Furthermore, a strict quality control system is established during the production process:

[0025] Inspect each batch of raw materials, including core material and wall material, including but not limited to purity, component content and physical properties;

[0026] Monitor every key link in the production process, including but not limited to droplet size monitoring during microencapsulation, pH value and temperature monitoring during curing, and record relevant data in detail;

[0027] The finished blasting beads are fully tested, including but not limited to particle size distribution, shell integrity and core material content. When all test items meet the predetermined standards, the batch of products is judged to be qualified products. If one item fails, production will be stopped immediately, the source of the problem will be traced, the production process parameters will be adjusted, and small-batch trial production will be carried out again until the product is qualified.

[0028] Beneficial Effects

[0029] Compared with the known public technology, the technical solution provided by the present invention has the following advantages:

[0030] Beneficial effects:

[0031] 1. The present invention can monitor and precisely control the droplet size distribution in real time through the coordinated use of high-precision microfluidics equipment and laser particle size analyzer, ensuring that more than 96% of the droplet size is within the ideal range of 0.5-2.0 mm. This technology of precisely controlling particle size greatly improves the uniformity and consistency of the small bursting bead products, making the final product excellent in appearance, taste and release performance, meeting the high-quality requirements of the high-end market for small bursting bead products.

[0032] 2. In the curing process, the present invention ensures the stable progress of the curing reaction by accurately controlling the addition amount of the curing agent and the reaction conditions, combined with the real-time monitoring and adjustment of the temperature sensor and the pH sensor, and forms a solid and uniform wall material shell. At the same time, in the cleaning process, a low-temperature centrifugal cleaning device is combined with deionized water circulation cleaning to effectively remove impurities in the product. After cleaning, the impurity content is less than 8 mg / L, ensuring the purity of the product. In addition, through the steps of nitrogen blowing and vacuum drying, the moisture content in the product is further reduced, and the stability and safety of the product are improved. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Example 1

[0036] (I) Material preparation:

[0037] Core material: Liquid natural fragrances containing specific functional ingredients and with volatility are selected as core materials. First, gas chromatography-mass spectrometry (GC-MS) is used to detect the purity of the liquid natural fragrance. After multiple tests and analyses, the purity of the liquid natural fragrance reaches 99.5%. In a sealed environment, the temperature is precisely controlled at 5°C by a temperature control system for storage and preparation. During the preparation process, high-performance liquid chromatography (HPLC) analysis is used to accurately control the proportion of each component, and the error is controlled within ±0.3%. For example, the target value of the content of the main active ingredient A is 30%, and the actual content is 29.8% after HPLC detection. The target value is finally reached by adding an appropriate amount of high-concentration active ingredient A standard. After the preparation is completed, it is filtered with a microporous filter membrane with a pore size of 0.3μm to remove the existing tiny particle impurities. Before filtration, the number of tiny particles in the solution is detected by a particle counter, which is about 500 / mL. After filtration, it is tested again, and the number of tiny particles is reduced to less than 10 / mL, which effectively ensures the purity of the core material.

[0038] Wall material: accurately weigh edible gelatin and gum arabic in a mass ratio of 2.5:1, add appropriate amount of deionized water, and dissolve under stirring at a temperature of 55°C and a speed of 250 revolutions per minute for 75 minutes to form a uniform solution. Use vacuum degassing equipment to degas for 15 minutes at a vacuum degree of -0.09MPa to remove bubbles in the solution. After degassing, use a viscosity meter to detect the viscosity of the solution. After multiple measurements, the solution viscosity is stabilized at 25mPa·s.

[0039] (II) Microencapsulation process:

[0040] A high-precision microfluidic device was selected and fully calibrated and debugged before use. The number of air dust particles in the reaction area was controlled below 8,000 per cubic meter. This was achieved through a high-efficiency filter in the air purification equipment. The core material was injected into the wall material solution at a frequency of 150 times per second. The temperature was controlled at 27°C and the stirring speed was 400 revolutions per minute. The droplet size distribution was monitored in real time using a laser particle size analyzer. In the early stage of the microencapsulation process, the droplet size distribution was wide, and some droplets had a size greater than 2.0 mm. At this time, the pressure of the microfluidic device was increased by 0.7 MPa / time; if the droplet size was less than 0.5 mm, the pressure was reduced by 0.4 MPa / time. After multiple adjustments and monitoring, it was finally ensured that more than 96% of the droplet size was within the range of 0.5-2.0 mm. At the same time, a high-speed camera was used to shoot the droplet formation process at a speed of 500 frames per second, and the droplet morphology and particle size changes were dynamically analyzed in combination with image analysis software to further assist in the precise control of the microfluidic device pressure.

[0041] (III) Curing process:

[0042] Add curing agent glutaraldehyde to the mixed solution containing droplets, the added amount is 0.7% of the wall material weight, and add it at a dripping speed of 3 drops per minute through a high-precision metering pump, and stir at a speed of 120 revolutions per minute. React for 45 minutes under an environment with a pH value of 6.5. During the reaction, the temperature and pH value changes of the reaction system are monitored in real time by a temperature sensor and a pH sensor. When the pH value deviates from 6.5±0.2, disodium hydrogen phosphate-citric acid buffer solution is automatically added for adjustment. For example, when the reaction is carried out for 20 minutes, the pH value rises to 6.7, and the control system immediately starts the metering pump and adds an appropriate amount of buffer solution to quickly restore the pH value to about 6.5, ensuring that the curing reaction proceeds stably and forms a solid and uniform wall material shell.

[0043] (IV) Cleaning process:

[0044] The solidified bead solution was transferred to a low-temperature centrifugal cleaning device, which used a variable frequency speed regulating motor with a set speed of 1200 revolutions per minute and a temperature of 6°C for 12 minutes. After cleaning, the supernatant was poured out and the solution was washed five times with deionized water. After each washing, an inductively coupled plasma mass spectrometer (ICP-MS) was used to detect the impurity content in the cleaning solution. After the first washing, the impurity content in the cleaning solution was about 15 mg / L. After five cycles of washing, the impurity content was reduced to 5 mg / L, which was lower than the qualified standard of 8 mg / L. After the cleaning was completed, nitrogen was used for drying, and the nitrogen pressure was controlled at 0.2 MPa for 10 minutes.

[0045] (V) Drying process:

[0046] The nitrogen-dried popping beads were placed in a vacuum drying oven with a vacuum degree of -0.095MPa and a temperature of 45°C for 4 hours. An infrared temperature sensor was installed in the vacuum drying oven to monitor the temperature at different positions of the popping beads in real time to ensure that the popping beads were evenly heated. During the drying process, a Karl Fischer moisture meter was used to monitor the moisture content of the popping beads. After drying for 2 hours, the moisture content was 6%. Drying was continued for 4 hours, and the moisture content was reduced to 4.2%, which was lower than the standard of 4.5%. The drying was stopped to obtain finished fine popping beads with a particle size of 0.5-2.0mm.

[0047] (VI) Finished product testing:

[0048] Particle size distribution test: The finished blasting beads were tested using a laser particle size analyzer. The results showed that 96.5% of the blasting beads had a particle size within the range of 0.5-2.0 mm, which met the expected requirements.

[0049] Shell integrity inspection: The surface of the beads was observed under a scanning electron microscope, and no obvious residual impurities, cracks or other defects were found, indicating that the shell was intact.

[0050] Core material content detection: The core material content is detected by nuclear magnetic resonance spectrometer. After calculation, the deviation between the core material content and the theoretical value is within ±2%, which meets the product quality standards.

[0051] Example 2

[0052] (I) Material preparation:

[0053] Core material: Another liquid extract containing functional ingredients and with low volatility was selected as the core material. The purity was 99.6% as tested by GC-MS. It was stored and formulated in a sealed environment at 4°C. HPLC was used to accurately control the proportion of ingredients with an error of ±0.2%. For example, the target content of the key ingredient B was 40%, and the actual content after formulation was 39.8%, which met the standard after fine-tuning. It was also filtered with a 0.3μm microporous membrane. The number of tiny particles before filtration was about 400 / mL, and it was reduced to less than 8 / mL after filtration.

[0054] Wall material: Gelatin and gum arabic were added to deionized water at a mass ratio of 2.5:1, and dissolved by stirring at 58°C and 280 revolutions per minute for 80 minutes. After the solution was formed, it was degassed at a vacuum degree of -0.092 MPa for 18 minutes, and the final viscosity was measured to be 26 mPa·s.

[0055] (II) Microencapsulation process:

[0056] In a purified environment (the number of dust particles is controlled below 7,000 per cubic meter), the microfluidic device injects the core material at a frequency of 160 times per second, the temperature is controlled at 28°C, the stirring speed is 420 revolutions per minute, and the laser particle size analyzer, high-speed camera and image analysis software are used to coordinate the control. Finally, 97% of the droplet particle size is in the range of 0.5-2.0mm.

[0057] (III) Curing process:

[0058] The amount of glutaraldehyde added was 0.8% of the wall material weight, the dropping speed was adjusted to 4 drops per minute, the stirring speed was 130 revolutions per minute, and the reaction was carried out for 48 minutes under a pH value of 6.6. With the help of temperature and pH sensors and a buffer solution adjustment system, the reaction was stable and a good shell was formed.

[0059] (IV) Cleaning process:

[0060] The speed of the low-temperature centrifugal cleaning equipment was set at 1300 rpm, the temperature was 7°C, the cleaning time was 15 minutes, and the cleaning cycle was 6 times. According to ICP-MS detection, the impurity content after the first cleaning was about 13 mg / L, and after the final cleaning, it dropped to 4 mg / L. The nitrogen drying pressure was 0.22 MPa, and the drying time was 12 minutes.

[0061] (V) Drying process:

[0062] Dry in a vacuum drying oven at a vacuum degree of -0.096MPa and a temperature of 48°C for 5 hours. Infrared temperature sensor monitoring ensures uniform heating. Karl Fischer moisture meter shows that the moisture content is 5% after 3 hours of drying and reaches 4% after 5 hours, then stop drying.

[0063] (VI) Finished product testing:

[0064] Particle size distribution test: 97.2% of the beads have a particle size between 0.5-2.0mm.

[0065] Shell integrity inspection: There are no obvious defects in the shell under the scanning electron microscope.

[0066] Core material content detection: The deviation between core material content and theoretical value is ±1.8%.

[0067] Comparative Example 1 (core material purity is low)

[0068] 1. Material preparation:

[0069] Core material: A liquid natural flavor similar to that in Example 1 was selected, but the purity was only 98%, and no strict ingredient ratio control and filtration treatment were performed.

[0070] Wall material: The same preparation method of gelatin and gum arabic solution as in Example 1.

[0071] (II) Microencapsulation process:

[0072] The microencapsulation equipment and parameters of Example 1 were used for operation. However, due to the low purity and untreated core material, the droplet size distribution was relatively dispersed, and only 85% of the droplet size was within the range of 0.5-2.0 mm.

[0073] (III) Curing process:

[0074] The amount of glutaraldehyde added and the operation were the same as in Example 1, but due to the droplet size problem, the uniformity of the shell after curing was poor.

[0075] (IV) Cleaning process:

[0076] The cleaning process parameters were the same as those in Example 1, but due to the large amount of impurities in the early stage, the impurity content after the final cleaning was still as high as 12 mg / L.

[0077] (V) Drying process:

[0078] The drying parameters were the same as those in Example 1, and the moisture content after drying was 5.5%.

[0079] (VI) Finished product testing:

[0080] Particle size distribution test: 85% of the burst beads have a particle size range of 0.5-2.0mm, which does not meet the requirements.

[0081] Shell integrity inspection: The shell has some defects and weak points.

[0082] Core material content detection: The deviation between core material content and theoretical value reaches ±5%.

[0083] Comparative Example 2 (abnormal wall material viscosity)

[0084] 1. Material preparation:

[0085] Core material: The core material processing method is the same as that in Example 1.

[0086] Wall material: When preparing the wall material solution, the stirring time was shortened to 60 min, resulting in a solution viscosity of only 20 mPa·s.

[0087] (II) Microencapsulation process:

[0088] During the microencapsulation process, due to the low viscosity of the wall material, it is difficult to effectively wrap the core material, and a large number of droplets have a particle size less than 0.5 mm, and only 70% of the droplets have a particle size within the range of 0.5-2.0 mm.

[0089] (III) Curing process:

[0090] Although the curing operation is carried out, the shell is easy to break after curing due to the poor wrapping effect.

[0091] (IV) Cleaning process:

[0092] The cleaning is difficult and many impurities remain. The final impurity content after cleaning is 10 mg / L.

[0093] (V) Drying process:

[0094] The moisture content after drying is 5%, but the beads are prone to sticking together.

[0095] (VI) Finished product testing:

[0096] Particle size distribution test: 70% of the burst beads have a particle size range of 0.5-2.0mm, which does not meet the standard.

[0097] Shell integrity test: Shell integrity is poor.

[0098] Core material content detection: The deviation between core material content and theoretical value is ±4%.

[0099] Comparative Example 3 (poor curing conditions)

[0100] 1. Material preparation:

[0101] Core material: same as the core material in Example 1.

[0102] Wall material: the same as in Example 1.

[0103] (II) Microencapsulation process:

[0104] The microencapsulation process proceeded normally, and the droplet size was controlled to be more than 96% in the range of 0.5-2.0 mm.

[0105] (III) Curing process:

[0106] The amount of glutaraldehyde added was inaccurate, accounting for only 0.5% of the wall material quality, and the pH value was not monitored and adjusted. The pH value fluctuated greatly during the reaction, resulting in incomplete curing and low shell strength.

[0107] (IV) Cleaning process:

[0108] The impurity content after cleaning was 8 mg / L, but due to the shell strength problem, some of the beads were damaged during the cleaning process.

[0109] (V) Drying process:

[0110] After drying, the moisture content is 4.8%, but the shape of the popping beads is irregular.

[0111] (VI) Finished product testing:

[0112] Particle size distribution test: 96% of the beads have a particle size range of 0.5-2.0mm, but some of the beads are deformed.

[0113] Shell integrity inspection: The shell has damage and weak points.

[0114] Core material content detection: The deviation between core material content and theoretical value is ±3%.

[0115] The data comparison is shown in the table:

[0116]

[0117] Through the detailed description and data comparison of the above embodiments and comparative examples, it can be clearly seen that the method for producing fine blasting beads of the present invention can prepare high-quality products under the condition of strict control of various parameters, and when the key steps or material parameters deviate from the standards, the product quality will be significantly reduced, which fully reflects the scientific nature and superiority of the method of the present invention. In the actual production process, the process parameters and operating steps in the embodiments should be strictly followed to ensure that the quality and performance of the fine blasting beads meet the requirements.

[0118] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for making small explosive beads, characterized in that: The preparation method comprises the following steps: First, prepare the core material and wall material raw materials. The core material is a liquid substance containing specific functional ingredients. The purity is tested by gas chromatography-mass spectrometry to ensure that the purity reaches 99.5%. Edible gelatin and gum arabic are used as the wall material and are prepared at a mass ratio of 2.5:

1. Next, the microencapsulation technology is used to inject the core material into the wall material solution at a frequency of 150 times per second through a high-precision microfluidic device. At the same time, the temperature is controlled at 27°C and the stirring speed is 400 revolutions per minute, so that the core material forms tiny droplets in the wall material solution. The droplet size distribution is monitored in real time using a laser particle size analyzer. When the particle size is greater than 2.0 mm, the pressure of the microfluidic device is increased by 0.7 MPa / time, and when the particle size is less than 0.5 mm, the pressure is reduced by 0.4 MPa / time, ensuring that more than 96% of the droplet size is between 0.5 and 2.0 mm. Subsequently, a curing agent is added to the mixed solution containing the droplets. The curing agent is glutaraldehyde, and the addition amount is 0.7% of the weight of the wall material. The dropping speed is 3 drops per minute. At the same time, the mixture is stirred at a speed of 120 revolutions per minute. The mixture is reacted for 45 minutes in an environment with a pH value of 6.5, so that the wall material forms a shell on the surface of the core material. Finally, a low-temperature centrifugal cleaning device is used to clean at a speed of 1200 revolutions per minute and a temperature of 6°C for 12 minutes, and then deionized water is used for cyclic cleaning 5 times. The cleaning liquid is considered qualified if the impurity content is less than 8 mg / L after cleaning. After cleaning, it is blown dry with nitrogen and then placed in a vacuum drying oven with a vacuum degree of -0.095 MPa and a temperature of 45°C for 4 hours. A Karl Fischer moisture meter is used for monitoring. When the water content is lower than 4.5%, the drying is stopped to obtain fine burst beads with a particle size of 0.5-2.0 mm.

2. The method for making small explosive beads according to claim 1, characterized in that: The preparation process of the core material further includes: pre-treating the core material raw material, wherein the core material is a liquid substance containing volatile components, and is stored and prepared in a sealed environment at a temperature controlled at 5°C. During the preparation process, high performance liquid chromatography analysis is used to accurately control the proportion of each component, and the error is controlled within ±0.3%. The pre-treated core material is filtered using a microporous filter membrane with a pore size of 0.3μm to remove the tiny particle impurities present.

3. The method for making small explosive beads according to claim 1, characterized in that: The preparation process of the wall material further includes: adding gelatin and gum arabic into deionized water at a mass ratio of 2.5:1, stirring and dissolving at a temperature of 55° C. and a speed of 250 revolutions per minute for 75 minutes to form a uniform solution, using a vacuum degassing device to degas for 15 minutes at a vacuum degree of -0.09 MPa to remove bubbles in the solution, and after degassing, testing the viscosity of the solution with a viscosity meter to ensure that its viscosity is 25 mPa·s.

4. The method for making small explosive beads according to claim 1, characterized in that: During the microencapsulation process, the number of air dust particles in the reaction area is controlled below 8,000 per cubic meter through air purification equipment. At the same time, a high-speed camera is used to capture the droplet formation process at a speed of 500 frames per second. The droplet morphology and particle size changes are dynamically analyzed using image analysis software to further accurately control the pressure of the microjet equipment.

5. The method for making small explosive beads according to claim 1, characterized in that: During the curing process, the temperature and pH value changes of the reaction system are monitored in real time by a temperature sensor and a pH sensor. When the pH value deviates from 6.5±0.2, disodium hydrogen phosphate-citric acid buffer solution is automatically added for adjustment to ensure that the curing reaction proceeds stably and forms a solid and uniform wall material shell.

6. The method for making small explosive beads according to claim 1, characterized in that: During the cleaning process, the low-temperature centrifugal cleaning equipment uses a variable frequency speed regulating motor to ensure stable rotation speed during the cleaning process. After the cleaning is completed, the surface of the beads is observed by a scanning electron microscope to ensure that there are no residual impurities. When nitrogen is used for drying, the nitrogen pressure is controlled at 0.2MPa and the drying time is 10 minutes.

7. The method for making small explosive beads according to claim 1, characterized in that: An infrared temperature sensor is arranged in the vacuum drying box to monitor the temperature at different positions of the blasting beads in real time to ensure that the blasting beads are heated evenly. After drying, an electronic universal material testing machine is used to test the strength of the blasting bead shell, and a nuclear magnetic resonance spectrometer is used to test the core material content to ensure that the finished blasting beads meet the requirements of a particle size of 0.5-2.0 mm and various performance indicators are qualified.

8. The method for making small explosive beads according to any one of claims 1 to 7, characterized in that: During the entire production process, the production equipment is regularly maintained and calibrated. The mechanical parts of the microfluidic equipment, stirring device and centrifugal cleaning equipment are inspected and maintained once a week, including but not limited to checking the wear of the transmission parts and the sealing of the sealing parts. The measuring instruments of the equipment, including but not limited to pressure sensors, temperature sensors and viscometers, are calibrated monthly using standard measuring instruments to ensure that the error of the measurement data is within ±0.5%.

9. The method for making small explosive beads according to any one of claims 1 to 7, characterized in that: Establish a strict quality control system during the production process: Inspect each batch of raw materials, including core material and wall material, including but not limited to purity, component content and physical properties; Monitor every key link in the production process, including but not limited to droplet size monitoring during microencapsulation, pH value and temperature monitoring during curing, and record relevant data in detail; The finished blasting beads are fully tested, including but not limited to particle size distribution, shell integrity and core material content. When all test items meet the predetermined standards, the batch of products is judged to be qualified products. If one item fails, production will be stopped immediately, the source of the problem will be traced, the production process parameters will be adjusted, and small-batch trial production will be carried out again until the product is qualified.

Citation Information

Patent Citations

  • Oily cooling liquid for preparing high-density essence blasting beads, application of oily cooling liquid and preparation method of high-density essence blasting beads

    CN112920780A

  • Preparation device of one-bag four-pair inner nuclear blasting bead

    CN117816063A

  • Preparation method of microcapsule-containing cigarette blasting bead

    CN117816064A

  • Method and apparatus for manufacturing microcapsule sheet

    JP2007275812A

  • Apparatus and Method for Using Tetrazine-Based Energetic Material

    US20090301601A1